Transformation of HR Management by Artificial Intelligence: A Study on PT Cisarua Mountain Dairy - Sri Wahyuni, Neng Ayu; Agung, Syahrum; Syahdiany, Geny (Educational Researcher Journal, 2026)
This study examines the role of Artificial Intelligence (AI) as a catalyst in the transformation of the strategic function of Human Resource Management (HRM) at PT Cisarua Mountain Dairy, an entity in the Fast-Moving Consumer Goods (FMCG) industry. The research background moves from the imperative of digital transformation that drives the evolution of MSDM from a conventional administrative model to a data-driven and predictive paradigm. Using a qualitative approach and instrumental case study design, this study explores the implementation dimensions, operational-strategic impacts, and complexity of challenges in the adoption of AI technology in the HR domain. Data collection was conducted through triangulation of methods, including semi-structured interviews with key informants (HR management, recruitment practitioners, and technologists), non-participant observations, as well as analysis of policy documents and internal digital artifacts. The research findings identify two main domains of AI adoption: (1) optimization of the talent acquisition process through algorithm-based screening and candidate matching systems, and (2) the development of people analytics systems for predictive modeling related to employee retention and development planning. The implementation has an impact on improving process efficiency, reducing bias in selection, and more precise analytical capacity. However, this study also reveals the existence of a significant implementation gap, which is represented by challenges in the form of organizational cultural resistance to automation, digital literacy gap, and ethical dilemmas around data privacy, algorithmic transparency), and accountability of decision-making by machines. This study makes a conceptual contribution by offering a contextual perspective on the transformation of digital HR in a large-scale national enterprise environment, as well as practical implications for the formulation of smart technology integration roadmaps and policies in talent management practices